The epidemiology of East Coast Fever in Malawi Zebu cattle and the economics of tick-borne disease control in Malawi - Soldan, Andrew William (The University of Edinburgh, 2009)
Morbidity, mortality and seroconversion to Theileria parva were studied in Malawi zebu cattle in six areas in the same ecological zone. A total of 3,257 animals were intensively monitored over a period of three years. Strategic tick control was carried out in four areas and no tick control was performed in a further two areas. Strenuous efforts were made to diagnose illness and deaths in the cattle.

The seasonal fluctuations in numbers of ticks on the cattle were observed at fourweekly intervals for three-and-a half years. Productivity of the cattle belonging to 143 farmers in the six areas was also monitored. Seroconversion to Cowdria ruminantium was monitored for the first year of the study.

Strategic dipping using nine immersions, at two-week intervals, from December to March gave almost complete control of R. appendiculatus but the numbers of B. microplus and A. variegatum were similar in dipped and undipped animals.

One undipped area was in an epidemiologically unstable state with respect to East Coast fever (ECF) due to prior dipping. East Coast fever mortality and morbidity were low in the first year after the cessation of dipping but rose over the second and third year until 46% of calves died ofECF before reaching one year of age. In the other undipped area ECF mortality and morbidity were low for all three years, despite high T. parva seroconversion rates. Dipping had ceased three years before the study began and it was concluded that this area was in a stable state with respect to ECF.

Strategic dipping in the other four areas caused very low ECF morbidity and mortality, as determined by comparison with the undipped control cattle. ECF mortality in strategically dipped calves was zero in most areas for most years.

Adult R. appendiculatus were responsible for most ofthe T. parva transmission causing clinical disease with nymphs responsible for a significant amount of sub¬ clinical infection. The existence of enzootic stability to ECF in an undipped area without continuous adult R. appendiculatus activity was demonstrated and the significance of nymphal transmission to the maintenance of this stability is discussed.

The costs and benefits of various tick-borne disease control strategies were calculated. Policies of vaccination or strategic dipping where tank construction was necessary were significantly less cost effective than policies involving stopping dipping or the continuation of strategic dipping at an existing tank. The most costeffective option would be to stop dipping and accept mortalities while endemic stability becomes established. This could however have a large social cost due to mortality in the early years.